Penerapan Teknik Penerjemahan dalam Puisi Borrowed Body Terjemahan Harry Aveling: Penelitian - Prisnalia, Yuni; Sitinjak, Shenny Ayunuri Beata (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the application of translation techniques in Joko Pinurbo’s poem Tubuh Pinjaman, translated by Harry Aveling as Borrowed Body. Using a descriptive qualitative method and the translation techniques proposed by Molina and Albir (2002), the study identifies several dominant strategies, including literal translation, modulation, borrowing, amplification, generalization, and transposition. These techniques help maintain the poetic meaning, emotional nuances, and symbolic representations within the poem. Through the appropriate application of translation strategies, the translator successfully conveys the philosophical and spiritual messages of the source text to English readers.